Selected issues in corporate governance : regional and country experiences (UN New YorkUS, 2003)
Presents selected issues in corporate governance. Examines corporate governance in the European Union; in the Eastern, Central and Southern African regions; and in Malaysia.
Keywords: GOVERNANCE